2021
DOI: 10.2147/ijwh.s334269
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Successful Vaginal Birth After a Primary Cesarean Section in Women with an Optimal Inter-Delivery Interval

Abstract: Purpose: We sought to determine the success rate of VBAC and factors associated with achieving VBAC at a referral hospital in the Democratic Republic of Congo in women with a subsequent pregnancy greater than or equal to 18 months from their primary cesarean section (CS). Patients and Methods: Patients were included for participation if they had an interdelivery interval (IDI) of at least 18 months from their primary CS, accepted TOLAC, and had no contraindications. Information was collected about patients' de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
3
7
0
4
Order By: Relevance
“…El PVPC es deseable; además, los resultados de este estudio y otras investigaciones previas han mostrado resultados exitosos y seguros (3,6,(9)(10)(11)(12) . El propósito de nuestro estudio fue identificar los factores que aumentan la tasa de éxito y reducen la morbimortalidad materna y perinatal, las cuales podrían complicar la resultante de la prueba de trabajo de parto en pacientes con cesárea previa.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…El PVPC es deseable; además, los resultados de este estudio y otras investigaciones previas han mostrado resultados exitosos y seguros (3,6,(9)(10)(11)(12) . El propósito de nuestro estudio fue identificar los factores que aumentan la tasa de éxito y reducen la morbimortalidad materna y perinatal, las cuales podrían complicar la resultante de la prueba de trabajo de parto en pacientes con cesárea previa.…”
Section: Discussionunclassified
“…La tasa de PVPC en esta investigación fue de 67,4%, lo que la ubica dentro del rango sugerido entre 60% y 80%, y es ligeramente mayor que lo encontrado en investigaciones previas (6,(8)(9)(10)(11)(12) . Las diferencias observadas en informes previos pueden reflejar los efectos de varios factores.…”
Section: Grupounclassified
See 1 more Smart Citation
“…17 However, no significant difference was observed in the spontaneous onset of labour and the need for induction and augmentation of labour for an inter-pregnancy interval in our study. A few systemic reviews and meta-analysis, [18][19][20] done internationally and locally were available on the predictors of a successful VBAC; however, no local studies were available to determine the influence of shorter interpregnancy interval on successful vaginal birth prior to cesarean section; thus, we conducted this study on the local population. Our study concluded that with increasing inter-pregnancy interval the chances of a successful VBAC increase (p=0.001) with fewer reported complications.…”
Section: Discussionmentioning
confidence: 99%
“…En el 2007, Grobman creo un nomograma de predicción, cimentado en factores de la primera atención prenatal, como "edad de la madre, IMC, etnia, parto vaginal previo, parto vaginal exitoso tras cesárea y recurrencia de indicación de cesárea primaria". Posteriormente, en el 2009 se incluyeron factores para ingreso a sala de parto, como el índice de masa corporal al parto, preeclampsia y edad gestacional al nacimiento (19,20). La suma total de estos factores oscilará entre 0 y 90, que representan el 1 y 99% de probabilidades de parto vaginal exitoso, con un punto de corte de 50 y 60% (21).…”
unclassified